Factores biológicos, sociales y paisajísticos del area de conservación municipal bosque de huamantanga – distrito de jaen para el desarrollo del ecoturismo - Romero Gerónimo, Alvaro (2014)
This final report entitled FACTORS BIOLOGICAL, SOCIAL AND LANDSCAPING OF MUNICIPAL FOREST CONSERVATION AREA HUAMANTANGA - JAÉN DISTRICT DEVELOPMENT OF ECO-TOURISM. Its field of study natural tourist resources ecotourism the ACM-BH Jaén District, located in the province of Jaén, Region, Cajamarca. To carry out the research took into account three points, the variety of natural tourism resources of flora and fauna, the positive attitude of the communities in the buffer zone and the diversity of landscapes in the ACM – BH. ACM-Forest Huamantanga was chosen because it has tourism resources managed in the best way tourist influx could generate national and international level for the purpose mentioned above, it is necessary to identify the resources of the area for the development of ecotourismo. It also explains, the positive attitude of the communities that make up the buffer zone against the development of ecotourism in the area explained. I will talk about two kinds of landscapes, open and closed with close viewing by the presence of dense vegetation that could attract tourists and psychological satisfaction having a combination of sensory components such as shapes, smell, color, light, texture, sound and temperature as which becomes a key factor to develop ecotourism. The last I conclude that the Conservation Area Municipal Forest Huamantanga has elements favorable for the development of ecotourism in natural tourism resources , the same to be utilized in a planned and organized and thus develop new tourism products such as eco-tourism circuit different conventional boosting tourism in the North Eastern of the country.